2018
DOI: 10.1007/s00106-018-0499-0
|View full text |Cite
|
Sign up to set email alerts
|

Staging von Oropharynxkarzinomen

Abstract: Clinical trials will have to show whether deescalation strategies regarding p16-positive carcinomas are supported by the changes made in the TNM staging system. A prospective multicenter study should examine the universal applicability, the appropriateness for all sublocations, as well as the prognostic significance of the current edition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In addition to the widely used diagnostic methods involved in postoperative histopathologic examination, various imaging techniques can be applied, such as ultrasound, magnetic resonance imaging (MRI), and computed tomography (CT). Clinical diagnosis of ENE of lymph node metastases presupposes that clear, defined criteria are met (8). Clinical or radiologic signs of tumor invasion alone (including the skin and surrounding soft tissue) as well as clinical symptoms of neural involvement (e.g., paresis of cranial nerves) are defined as clinical ENE in the new TNM classification (9).…”
Section: Imaging and Clinical Predictors In Diagnosing Extranodal Extmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the widely used diagnostic methods involved in postoperative histopathologic examination, various imaging techniques can be applied, such as ultrasound, magnetic resonance imaging (MRI), and computed tomography (CT). Clinical diagnosis of ENE of lymph node metastases presupposes that clear, defined criteria are met (8). Clinical or radiologic signs of tumor invasion alone (including the skin and surrounding soft tissue) as well as clinical symptoms of neural involvement (e.g., paresis of cranial nerves) are defined as clinical ENE in the new TNM classification (9).…”
Section: Imaging and Clinical Predictors In Diagnosing Extranodal Extmentioning
confidence: 99%
“…The following criteria are used for radiologic diagnosis of ENE for both CT and MRI: presence of irregular nodal capsular enhancement, loss of distinct nodal margins and infiltration into adjacent structures (fatty tissue, muscle, blood vessels) (1,10,11). Generally speaking, however, the limited sensitivity and specificity of the methods used in relation to the clinical diagnosis of ENE need to be discussed (8). For example, Steinkamp et al showed in several publications a sensitivity of ∼80.9% with specificity of 72.2% for CT investigations and sensitivity of ∼74.4% and specificity of 72.2% for MRI imaging (1,12,13).…”
Section: Imaging and Clinical Predictors In Diagnosing Extranodal Extmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in the univariate Cox analysis, tumor stage, N stage, and risk level are all poor prognostic indicators of HNSCC. As the traditional tumor stage has certain limitations in predicting the prognosis of HNSCC ( Beltz et al, 2018 ), we established a prognostic model that combines six-gene signatures related to metastasis with tumor stage in HNSCC using multivariate Cox analysis. Next, the nomogram constructed based on this model provided a more intuitive evaluation tool.…”
Section: Discussionmentioning
confidence: 99%
“…In the new World Health Organization (WHO) classification from 2017 [1,2], oropharyngeal tumors are found to be so important, that they are separated in a new chapter, being divided from tumors in the oral cavity, in which they were incorporated in previous classification from 2005. These tumors are now classified as p16 positive, associated with Human Papillomavirus (HPV) infection [3,4,5], and p16 negative, associated with long term cigarette smoking and alcohol abuse [6,7].…”
Section: Introductionmentioning
confidence: 99%